Disease Severity and Care Practices of COVID-19 Infected Nurses: A Cross-sectional Study - Khatri, Pratima; Tamrakar Sauami, Jamuna (Journal of Nursing Education of Nepal, 2024)
Covid-19 has been causing serious medical complications resulting from mild to critical illness, including death. Nurses caring for patients with COVID-19 were getting infected themselves and posing a risk to their families. This study aimed to find out the severity of the disease and care practices of COVID-19-infected nurses Methods: A cross-sectional study design among 418 nurses from COVID-designated hospitals was contact personally to collect data through a self-administered questionnaire in 2021 after taking Ethical approval from NHRC. The SPSS software version 16 was used to process and analyze the data. Results: The mean age of participants was 29.69, ranging from 19 to 68 years. Among all female participants, 335 (80.1%) were staff nurses, 236 (56.5%) were working in the COVID-designated area, and only 17% received training. Likewise, participants who were in isolation were 322 (77%), while 8 (1.9%) were admitted and treated in the critical care unit, and 26 (6.2%) received antiviral therapy. Additionally, their practices showed wearing PPE at>90%, following donning and doffing 87%, and eating nutritious food 86%. Music was a relaxation technique for 60%, followed by yoga/meditation for 43%. The Chi-square test showed no association between disease severity and care practices of COVID-19 infection. Conclusion: The majority of nurses experienced mild to moderate health issues due to COVID-19 infection. Whereas their care practices about wearing PPE, donning, and doffing were good, and no association of disease severity and care practice. Therefore, further exploration is needed to identify the factors associated with disease severity.